Mariano Soler: activista ultramontano transnacional (1846-1908). Una historia del internacionalismo católico desde América Latina (2025)
The study addresses the notion of “desire”—synthesized by Augustine in Confessions 1,1—not in itself, but as rethought by Edith Stein, a powerful thinker and profound expert on Augustinian thought. Although she frequently quotes Augustine in her work Endliches und Ewiges Sein, she does not directly address the notion of “desire” of the Bishop of Hippo, but her analyses nervertheless support the Augustinian basis of this human phenomenon and the undisputed relevance of Augustine today.